Jual Beli Harta Wakaf Bekas Bongkaran Masjid Perspektif Ulama Syafi’iyah - Eka Nur Safitri, Suad Fikriawan, Nafi’ah (Al-Musthofa: Journal of Sharia Economics, 2020)
The rewards that will not be broken after death; shodaqah Jariyah, useful knowledge and pious children who pray for their parents. Among Islamic schools of thought, mosques have their own laws that are different from those of other waqf items. According to the Syafi'iyah scholars, property that is waqf regardless of the wakif belongs to Allah and means to hold onto property forever. The method used is qualitative, or research methods based on the philosophy of postpositivism, or interpretive and constructive paradigms, which view social reality as a unified whole. The results showed that the difference between istinbat among the Syafi'iyah ulama, the writer tended to be the opinion of the Syafi'iyah ulama who allowed the sale and purchase of waqf items from the demolition of mosques. Based on the reality in the community, buying and selling of used waqf objects from the mosque is allowed because it does not bring benefits to waqf and with this sale it will bring new benefits to waqf assets, and this is inseparable from the aspect of the benefit of the people.